The organizational domain in HTA reports: towards a technology-oriented assessment. (5th November 2019) - Cacciatore, Pasquale; Specchia, Maria Lucia; Solinas, Maria Giuliana; Ricciardi, Walter; Damiani, Gianfranco
Abstract: Background: Organizational aspects in Health Technology Assessment (HTA) reports play a significant role in managing policies and strategies to implement new health technologies. The organizational domain, however, is often under-represented in HTA reports. This study explored how organizational assessment is carried out in HTA reports and designed a new perspective through an empirical approach after the comparison with EUnetHTA's Core Model 3.0. Methods: Full HTA reports were extracted from the websites of members of International Network of Agencies for HTA and the aspects relating to the organizational assessment were analysed. HTA reports were classified into 4 typologies of technologies (device, diagnosis/screening, intervention and organizational procedures) and organizational aspects described were explored through a framework of 5 domains and 15 subdomains from Core Model. Specific Multiple Correspondence Analyses were carried out to identify technology-related domains for organizational assessment in reports. Results: The analysis showed that domains and subdomains of Core Model were not covered homogeneously by the organizational assessments in the HTA reports. Through Multiple Correspondence Analyses, four new technology-related dimensions were identified and named according to the Core Model's subdomains in the four new clusters. Conclusions: This study analyzed the significance of organizational assessments in current literature and the challenges of improving this domain in HTA reports. Through an empirical analysis, we proposed a new methodology to cover the most relevant aspects of organizational appraisal according to new domains to promote support to the assessment of organizational issues in reports and fulfil the needs of future HTA research.